Probiotic Innovation: Optimizing Coconut Water Kefir for Health and Consumer Acceptance - I Nyoman, Sucipta; I Putu, Suparthana; Ketut, Suriasih; Wayan, Citra Wulan Sucipta Putri (Department of Technology of Agricultural product (THP) Jambi University, 2026)
Coconut water kefir is a non-dairy probiotic beverage produced through the fermentation of coconut water using kefir starter cultures. Unlike milk kefir, coconut water kefir exhibits distinct physicochemical and microbiological characteristics, necessitating specific quality optimization. This study evaluated the effects of sugar addition timing (before or after 24 h incubation) and storage duration (0–4 weeks) on the chemical (total acid, total sugar, pH, alcohol), physical (viscosity), microbiological (lactic acid bacteria, yeast, total microbes, Escherichia coli), and organoleptic properties of coconut water kefir. A quantitative descriptive approach with two replications was applied. The results indicated that sugar addition after incubation combined with two weeks of refrigerated storage provided the most balanced overall quality, considering physicochemical stability, probiotic viability, microbiological safety, and sensory acceptance. Under these conditions, the kefir exhibited total acidity of 0.16%, total sugar of 7.60%, pH 4.00, alcohol content of 0.33%, viscosity of 1.10 cP, lactic acid bacteria of 7.8 × 10⁷ CFU mL⁻¹, yeast of 1.7 × 10⁶ CFU mL⁻¹, total microbes of 2.6 × 10⁶ CFU mL⁻¹, and was negative for E. coli. Although the highest overall organoleptic score was observed at week 0, the two-week storage condition was selected as optimal due to its more favorable balance between functional quality and consumer acceptance (overall score 3.20 on a 5-point scale). These findings highlight the distinct characteristics of coconut water kefir compared to milk kefir and support the need for developing specific quality standards for water-based kefir beverages.